2021
DOI: 10.1038/s41598-021-99588-z
|View full text |Cite
|
Sign up to set email alerts
|

Free-moving Quantitative Gamma-ray Imaging

Abstract: The ability to map and estimate the activity of radiological source distributions in unknown three-dimensional environments has applications in the prevention and response to radiological accidents or threats as well as the enforcement and verification of international nuclear non-proliferation agreements. Such a capability requires well-characterized detector response functions, accurate time-dependent detector position and orientation data, a digitized representation of the surrounding 3D environment, and ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…7) detector response validation: we showed good agreement between data and our response models for the MiniPRISM detector in Ref. [22]. We performed an additional validation study with NG-LAMP and Na-22 check sources (which also emit at 511 keV), and found agreement between expected and measured effective areas to within ∼10%.…”
Section: Discussionsupporting
confidence: 59%
“…7) detector response validation: we showed good agreement between data and our response models for the MiniPRISM detector in Ref. [22]. We performed an additional validation study with NG-LAMP and Na-22 check sources (which also emit at 511 keV), and found agreement between expected and measured effective areas to within ∼10%.…”
Section: Discussionsupporting
confidence: 59%
“…Although the data are individually read out by detector, for this analysis the detector events were collected together as if the system were a single, monolithic detector to maintain simplicity and keep computation times manageable while demonstrating efficacy in modeling attenuation. A measurement-validated simulated response function in all 4π steradians was used when performing PSL [21], and the simulations used the actual configuration of 58 detectors used in the measurement. Only the responses for the 54 detectors that had adequate performance at the time were summed together and used in the analysis.…”
Section: Results For Experimental Datamentioning
confidence: 99%
“…However, the processing here has been done on a single CPU, which is the worst case scenario. In principle, the ray casting can be parallelized and run on GPUs, and a single PSL optimization has already been implemented on a GPU [21]. A better optimization procedure than a brute force grid search and better initial guesses based on contextual information should also be able to speed up evaluation time, and constraints from computer vision classification or operator input could further reduce the computational complexity and afford nearly real-time inference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations